PENGEMBANGAN MEDIA KOTAK CITA-CITA PORTABEL UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS III SD - Harahap, Rizka Khoirina; Faisal, F (Universitas Negeri Medan, 2024)
This research aims to determine the validity, practicality, and effectiveness of developing dream box media to increase learning motivation for class III of PAB 23 Patumbak Private Elementary School. This research is to provide a solution for students, namely that there are still many who do not focus on learning, they spend more time on unproductive things, this is due to the lack of motivation from teachers. The provision of motivation carried out by teachers is still not able to arouse students' enthusiasm for learning so that teaching and learning activities do not run as expected, efforts to clarify learning objectives and efforts to create a pleasant learning atmosphere are still not optimal, this is due to the limited capabilities and costs of teachers. This research is research and development (Research and Development) using the ADDIE Analysis, Design (Planning), Development (Development), Implementation (Implementation), and Evaluation (Evaluation) development model. The subjects in this research were students and teachers of class III of PAB 23 Patumbak Private Elementary School. Based on the research results obtained, media content expert validation in stage I obtained a score of 68.33% in the